2009
DOI: 10.1017/s0047279409990018
|View full text |Cite
|
Sign up to set email alerts
|

Researching Up? Interviews, Emotionality and Policy-Making Elites

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. of interviewing a particular public policy-making elite and examines how a particular 'public trauma' -that is, the damaging political fall-out of extremely negative news media coverage of the Parekh Report -inflected our research encounters. We argue that the openness with which many of the participants spoke about this traumatic experience suggests that the production of policy documents ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 34 publications
1
40
0
1
Order By: Relevance
“…politicians, civil servants, business leaders, etc.) and their views is challenging (Schoenberger 1991, Cochrane 1998, McDowell 1998, Elwood and Martin 2000, Kezar 2003, Smith 2006, Neal and McLaughlin 2009), and we found that it was more difficult to encourage such people to "break the frame" and look at their communities in new ways. The abstract language of zoning maps and other planning tools and rhetoric is, after all, the language of these actors.…”
Section: Discussionmentioning
confidence: 89%
“…politicians, civil servants, business leaders, etc.) and their views is challenging (Schoenberger 1991, Cochrane 1998, McDowell 1998, Elwood and Martin 2000, Kezar 2003, Smith 2006, Neal and McLaughlin 2009), and we found that it was more difficult to encourage such people to "break the frame" and look at their communities in new ways. The abstract language of zoning maps and other planning tools and rhetoric is, after all, the language of these actors.…”
Section: Discussionmentioning
confidence: 89%
“…As with calls to turn the research gaze upwards onto elites and the powerful the over-research argument tends to work on an interpretation of power as fixed and linear. But, as has been argued elsewhere (see for example Cochrane, 1998;Mohan, 1999;Neal and McLaughlin, 2009), reflections on research engagements with elites have illuminated instabilities and uncertainties about the location of power in research relations. Our emphasis on 'placed' participants' agency and our orientation towards co-productive research relationships in which we established 'circulations of communication ' (Sinha and Back 2014: 473) suggest that disproportionate research attention may allow the development of sustainable forms of research engagement.…”
Section: Discussionmentioning
confidence: 88%
“…In their reflections on researching elites Neal and McLaughlin (2009) (2013) show that not all people in Shatila were against the researchers because of what they saw as potential benefits, both personal and social, from the research process. It is to place-making processes and the constructed localities of our research that we now turn.…”
Section: Places and Re-presentations Of Placesmentioning
confidence: 99%
“…Accordingly, categories such as 'powerful elites' and 'powerless others' (Smith ibid) are meaningless without considering the extent to which elites can transfer their skills and power across borders (cf Riaño 2011;Neal and McLaughlin 2009). In the case of highly skilled migrant women I propose the term 'marginalized elites'.…”
Section: Highly Skilled Migrant Women and Positionalitymentioning
confidence: 99%
“…The conclusion questions what can be learned from the proposed methodology. Neal and McLaughlin (2009) make a distinction between researching powerful and non-powerful subjects and alert us to the difficulties of creating inclusive research relationships with powerful elites. If highly skilled migrants are understood as 'transnational elites' (Beaverstock 2005), are highly skilled migrant women also elite?…”
Section: Introductionmentioning
confidence: 99%